2021
DOI: 10.1002/clc.23747
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea therapy for cardiovascular risk reduction—Time for a rethink?

Abstract: Obstructive sleep apnea (OSA) is a highly prevalent and underdiagnosed medical condition, which is associated with various cardiovascular and metabolic diseases. The current mainstay of therapy is continuous positive airway pressure (CPAP); however, CPAP is known to be poorly accepted and tolerated by patients. In randomized controlled trials evaluating CPAP in cardiovascular outcomes, the average usage was less than 3.5 hours, which is below the 4 hours per night recommended to achieve a clinical benefit. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…20 Patients treated by CPAP and MAD experience reduced blood pressure and weight reduction. 18 At 6 months of treatment, CPAP and MAD improve depression and quality of life scores comparably. 21 Mitigation of sleep apnea symptoms is consistent with improvement in the apnea-hypopnea index.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…20 Patients treated by CPAP and MAD experience reduced blood pressure and weight reduction. 18 At 6 months of treatment, CPAP and MAD improve depression and quality of life scores comparably. 21 Mitigation of sleep apnea symptoms is consistent with improvement in the apnea-hypopnea index.…”
Section: Discussionmentioning
confidence: 95%
“…11 (CPAP) but more comfortable and convenient for the patient, thereby offering an option to which patients may more readily adhere. 18,19 Data from 34 randomized controlled trials found a greater than 50% reduction in the apnea-hypopnea index with MAD in adults with obstructive sleep apnea. 20 Patients treated by CPAP and MAD experience reduced blood pressure and weight reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies show a clear association between OSA and CVD prevalence and epidemiological studies show that OSA is associated with increased incidences of CVD [ 2 ]. However, three randomized controlled trials (RCT) tested the effect of CPAP on cardiovascular risk reduction for OSA patients, and all showed no improvement in cardiovascular end points [ 30 ]. We believe a vitally important step is to study intermediatory mechanisms of cardiovascular risk to establish mechanistic plausibility of the treatment.…”
Section: Discussionmentioning
confidence: 99%